2009
DOI: 10.1103/physrevb.79.081406
|View full text |Cite|
|
Sign up to set email alerts
|

Photovoltaic Hall effect in graphene

Abstract: Response of electronic systems in intense lights (AC electric fields) to DC source-drain fields is formulated with the Floquet method. We have then applied the formalism to graphene, for which we show that a non-linear effect of a circularly polarized light can open a gap in the Dirac cone, which leads to a photo-induced dc Hall current. This is numerically confirmed for a graphene ribbon attached to electrodes with the Keldysh Green's function.Comment: 5 pages, 3 figure

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
1,003
2
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,241 publications
(1,034 citation statements)
references
References 20 publications
24
1,003
2
5
Order By: Relevance
“…2b, red arrows) but not along k x , and asymmetry in the intensity of Floquet sidebands about k x = 0. The first observation is consistent with Floquet-Bloch theory on Dirac systems [29][30][31][32] . As the pump E-field is along the x-direction, the perturbing Hamiltonian commutes with the Dirac Hamiltonian corresponding to electrons with momentum along k x .…”
supporting
confidence: 77%
“…2b, red arrows) but not along k x , and asymmetry in the intensity of Floquet sidebands about k x = 0. The first observation is consistent with Floquet-Bloch theory on Dirac systems [29][30][31][32] . As the pump E-field is along the x-direction, the perturbing Hamiltonian commutes with the Dirac Hamiltonian corresponding to electrons with momentum along k x .…”
supporting
confidence: 77%
“…Floquet quasiparticles are an example of an explicit product of light-matter interaction [4][5][6]10,11 . Under periodic electromagnetic excitation with frequency Ω (panel c), electronic bands become dressed, which manifests itself as a 'Floquet' copy of the original band shifted in energy by hΩ [61][62][63][64][65] .…”
Section: Nature Materials Doi: 101038/nmat5017mentioning
confidence: 99%
“…Recent work has shown that non-trivial Berry phases can be engineered not just in bare electronic states but also in dressed states [4][5][6] . The basic mechanism involves hybridizing pairs of dressed bands (for example, with magnetic field or circularly polarized light) so that each acquires a non-trivial winding number, which produces protected edge modes (panel d).…”
Section: Nature Materials Doi: 101038/nmat5017mentioning
confidence: 99%
“…(2), corresponding to the case with focused light incident on a portion of an optical lattice modeled by Floquet theory . 8 We now turn to the case when the surface of the 3D TI is irradiated by circularly polarized light with vector potentialÂ…”
Section: Electron-photon Dressed States In Graphene and Topological Imentioning
confidence: 99%
“…6,7 The advantage of inducing a gap with circularly polarized light is it being tunable, i.e., the gap could be controlled by changing the intensity of the radiation. The effects of the gap opening were considered classically for both graphene 8,9 and TIs. 10,11 Additionally, there have been a number of studies using laser radiation on single layer 12 and bilayer 13 graphene as well as graphene nanoribbons 14,15 reporting the gap opening as the result of electron-photon interaction.…”
Section: Introductionmentioning
confidence: 99%